Health care-seeking from the traditional herbal healers in Denpasar City - Sri Yuniari; Ketut Suastika; Luh Seri Ani (Public Health and Preventive Medicine Archive, 2013)
Traditional herbal treatment is one of treatment efforts beyond medical science which is currently quite popular among people in Denpasar. Seeking health care from traditional herbal healers is not only has a positive impact but also negative ones. Excessive promotion in various media causes people to be less rational in choosing health care services. This study aims to determine the association between knowledge, attitudes, beliefs and media information with the health care-seeking from traditional herbal healers. The study design was analytic cross-sectional. Sample was consecutively selected from the population involving 129 people who have met the inclusion criteria. Data were collected by using questionnaire. Chi-square results showed that all variables examined were significantly associated with health care-seeking from the traditional herbal healers. Results from logistic regression indicated that only belief was significantly associated with the level of patient visits to traditional herbal healers (RP=6.57; 95%CI: 1.43-8.84, p=0.006 and R2=49.5%). Denpasar City Health Office should improved guidance and control the traditional herbal healers so as to provide a sense of security to the community.